Effect of cationic micelles on the decomposition of alpha-aminophenyl cephalosporins - Oliveira, Anselmo Gomes de [UNESP]; Rossanezzi, G. [UNESP]; Formariz, T. P. [UNESP]; Egito, E. S. T.; Scarpa, M. V. [UNESP] (Elsevier B.V., 2010)
The intramolecular rates of degradation of a-aminophenyl cephalopsorins were determined with and without hexadecyltrimethylammonium bromide (CTAB). Micellar-derived spectral shifts were used to measure the bind of the ionic forms as well as to determine the effect of CTAB on the apparent dissociation constant of the antibiotics. The rate of the degradation of cephalexin (Cp), cefadroxil (Cf), and cephradine (Cph), increased with surfactant concentration reaching a plateau at high surfactant concentrations. In the plateau region, the rate constant was salt sensitive decreasing with NaBr concentrations. These effects were quantitatively analyzed within the framework of the pseudo-phase model with explicit considerations of ion exchange. All the experimental results were fitted to this model. The intramolecular degradation of Cf. Cp and Cph was catalyzed by 96-, 59-, and 29-fold, respectively. A working hypothesis to rationalize these effects was suggested. The obtained results demonstrate that the quantitative analysis can be used to assess, predict and control the effects of surfactants on the drug stability. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: alpha-Aminophenyl cephalopsorins; Cationic micelles; Drug stability; Intramolecular degradation; Cephalosporins degradation